Virtual environment to co-create digital educational resources in higher education [Entorno virtual para cocrear recursos educativos digitales en la educación superior] (2020)
"This article presents an approach of a virtual learning environment, which through an online platform allows the co-creation of digital educational resources for higher education in Colombia. This proposal results from a research process oriented to the application of effective teaching-learning methodologies and strategies for university environments. Co-creation is approached as a significant method for the design of learning contents, due to the representative relationship among the actors involved in the resources production (user-designer), and the theoretical and experiential knowledge that each one has and is applied in a virtual environment. The main objective of the study is ""to implement a model for the co-creation and production of open educational contents through the usage of a virtual platform"", which is circumscribed in the qualitative perspective, from the hermeneutical methodological approach. As results and conclusions, it is stated that the concept of co-creation opens up multiple possibilities to create enriched processes, led and generated by both the teacher and the students. It is a two-way action where both profiles propose, produce, and distribute in order to generate educational resources and share interest and common knowledge. © 2020 Red Universitaria de Campus Virtuales. All rights reserved."